Exploring MBA student perceptions of their preparation and readiness for the profession after completing real-world industry projects. Issue 2 (July 2019) - Witt, Christine M.; Sandoe, Kent; Dunlap, Joanna C.; Leon, Kendall
Abstract: This paper describes the development and evaluation of a capstone project implemented in an MBA level Operations Management course being offered at an AACSB accredited College of Business in the Pacific Northwest. The capstone project was designed with two constructs that influence professional preparation: authentic learning and student choice. We surveyed 20 graduate business students to evaluate how the proposed artifact, The Process Improvement Capstone Project, supports student learning. Using a survey with six open-ended questions, students were asked to reflect on the project, their experience working with a real-world client, and their preparedness for the workforce. The authors mined the text of the survey responses and developed a co-occurrence network to identify potential relationships between terms that students used and the major constructs of the instructional design. The paper discusses implications for this correspondence in designing authentic projects that integrate industry partners in MBA classes. Highlights: Scaffolding assignments supports scheduling and focus. Providing students with autonomy increases student engagement. Students value collaboration, feeling that it enhances their learning. Authenticity enhances students' professional preparation.